UPTAKE OF METALS AND METALLOIDS BY CONYZA CANADENSIS L. FROM A THERMOELECTRIC POWER PLANT LANDFILL - Vukojević, Vesna; Trifković, Jelena; Krgović, Rada; Milojković-Opsenica, Dušanka; Marković, Marijana; Amaizah, Naser Ramdan R.; Mutić, Jelena (Archives of Biological Sciences, 2016)
Fourteen metals and metalloids were determined in Conyza canadensis L. harvested from the fly ash landfill of the thermoelectric power plant “Kolubara” (Serbia). Fly ash samples were collected together with the plant samples and subjected to sequential extraction according to the three-step sequential extraction scheme proposed by the Community Bureau of Reference (BCR; now the Standards, Measurements and Testing Program). The contents of metals and metalloids were determined by inductively coupled plasma optical emission spectrometry (ICP-OES) in plant root and the aboveground part and correlated with their contents in the fly ash samples. The bioconcentration factor (BCF) and translocation factors (TF) were calculated to access uptake of metals from fly ash and their translocation to the aboveground part. Results regarding As revealed that fly ash samples in the proximity of the active cassette had higher amounts of the element. Principal component analysis (PCA) showed that As had no impact on the classification of plant parts. BCF for As ranged from 1.44 to 23.8 and varied, depending on the investigated area; TF for As ranged from 0.43 to 2.61, indicating that the plant translocated As from root to shoot. In addition to As, Conyza canadensis L. exhibited efficient uptake of other metals from fly ash. According to the calculated BCF and TF, the plant retained Al, Fe and Cr in the root and translocated Zn, Cd, Cu and As from root to shoot in the course of the detoxifying process. DOI: 10.2298/ABS151011071V Key words: arsenic; bioaccumulation; bioconcentration factor; Conyza canadensis L.; fly ash Received: October 11, 2015; Revised: December 23, 2015; Accepted: December 24, 2015; Published online: August 5, 2016 How to cite this article: Vukojević V, Trifković J, Krgović R, Milojković-Opsenica D, Marković M, Amaizah NRR, Mutić J. Uptake of metals and metalloids by Conyza canadensis L. from a thermoelectric power plant landfill. Arch Biol Sci. 2016;68(4):829-35.